The influence of pulse modulated UV LEDs of different wavelengths on the photocatalytic degradation of atmospheric toluene and NO - Ehm, Clemens; Stephan, Dietmar (Frontiers in Catalysis, 2022)
Fluorescent tubes, a continuous source of UVA radiation, are increasingly being replaced by ultraviolet light-emitting diodes (UV LEDs or UVEDs), which emit an almost discrete spectrum (5 nm bandwidth). This creates both problems and opportunities from a photocatalytic point of view. In this paper, we report the influence of UVED radiation on the performance of an industrially produced TiO2 photocatalytic coating by measuring the degradation of nitrogen oxide (NO) and toluene (C6H5CH3) from a test atmosphere in a laboratory test setup. The influence of four commercially available UVED types (365 nm, 385 nm, 395 nm, and 415 nm) on the performance of a commonly used photocatalyst was compared. In a subsequent investigation, we switched from continuous to pulse-modulated LED operation and investigated its influence on the photocatalytic activity of the assembly. We could show that UVEDs are suitable replacements for fluorescent lamps when carefully chosen to the absorption spectrum of the used photocatalyst. In addition, the pulse width and pulse frequency modulation of the LED current show non-linear correlations with the resulting photocatalytic activity. The activity remains unexpectedly high with short pulse widths and low frequencies. By adjusting the control of the UVEDs accordingly, much energy can thus be saved during operation without reducing the catalytic activity.